2009
DOI: 10.1021/ja904343c
|View full text |Cite
|
Sign up to set email alerts
|

Heterolytic Reduction of Fatty Acid Hydroperoxides by Cytochrome c/Cardiolipin Complexes: Antioxidant Function in Mitochondria

Abstract: Cytochrome c (cyt c), a mitochondrial intermembrane electron shuttle between complexes III and IV, can, upon binding with an anionic phospholipid, cardiolipin (CL), act as a peroxidase that catalyzes cardiolipin oxidation. H(2)O(2) was considered as a source of oxidative equivalents for this reaction, which is essential for programmed cell death. Here we report that peroxidase cyt c/CL complexes can utilize free fatty acid hydroperoxides (FFA-OOH) at exceptionally high rates that are approximately 3 orders of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 17 publications
2
74
0
1
Order By: Relevance
“…The resultant peroxidase activity displays significant specificity toward CLs, yielding its highly diversified oxygenated species and their hydrolysis products, predominantly mono-lyso-CLs and oxygenated fatty acids, with signaling modalities (49 -51). CL hydroperoxides can be utilized by the peroxidase complex as an alternative (to H 2 O 2 ) source of oxidizing equivalents, thus "perpetuating" the functioning of the peroxidase cycle (43,47). Although the significance of the peroxidase activation of cytochrome c in apoptosis has been documented (18,20), the uniqueness of CLs as endogenous activators is not unequivocal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant peroxidase activity displays significant specificity toward CLs, yielding its highly diversified oxygenated species and their hydrolysis products, predominantly mono-lyso-CLs and oxygenated fatty acids, with signaling modalities (49 -51). CL hydroperoxides can be utilized by the peroxidase complex as an alternative (to H 2 O 2 ) source of oxidizing equivalents, thus "perpetuating" the functioning of the peroxidase cycle (43,47). Although the significance of the peroxidase activation of cytochrome c in apoptosis has been documented (18,20), the uniqueness of CLs as endogenous activators is not unequivocal.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to the H 2 O 2 source of oxidizing equivalents, we tested the fatty acid hydroperoxide, 13 S-hydroperoxy-9Z,11E-octadecadienoic acid (FFA-OOH). FFA-OOH and H 2 O 2 have different binding sites on the cytochrome c molecule: H 2 O 2 was found to occupy a site in the proximity to His 18 , whereas FFA-OOH binds to a different site, with the hydroperoxy group located in proximity to Arg 38 and His 33 (43). In line with previously reported data, FFA-OOHs were much better peroxidase substrates for cytochrome c/TOCL than H 2 O 2 , whereas the peroxidase activity of cytochrome c was only slightly increased by ␣-TOS and remained essentially unaffected by ␣-TOP (Fig.…”
Section: Interaction Sites Of ␣-Tos/␣-top On Cytochrome C-tomentioning
confidence: 99%
“…H 2 O 2 is thought to be the ROS mediating CL-peroxidation, which is catalyzed by the peroxidase activity of the complex CL-Cyt C. 42,43 A recent work by Belikova et al, 63 however, revealed that fatty acid hydroperoxides can also provide the oxidizing equivalents to the peroxidase complex that results in CL-peroxidation. Therefore, it is possible that fatty acid hydroperoxides hydrolyzed by phospholipase-mediated hydrolysis once translocated from the ER to the mitochondria, can directly mediate CL-peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…CL-bound cytc shows a non-native tertiary structure, a disrupted heme-Fe-Met80 distal bond [12][13][14][15][16][17], and a drastically reduced midpoint potential, which falls out of the range required for its physiological role [18]. Further, the cleavage of the distal Fe-Met80 bond endows cytc with a high affinity for CO and NO [19,20] and peroxidase activity [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The high reactivity of the penta-coordinated CL-cytc complex [11,19,20,26] prompted us to investigate the effect of CL on peroxynitrite isomerization by ferric cytc (cytc-Fe(III)). In the absence of CL, hexa-coordinated cytc does not catalyze peroxynitrite isomerization, even though it has been shown that peroxynitrite may induce the very slow nitration (30 min) of the solvent-exposed Tyr74 residue; this leads to the cleavage of the Fe-Met80 bond, which is substituted by a weak Fe-Lys72 ligation [29].…”
Section: Introductionmentioning
confidence: 99%